The material conception of religion among inmates in the Ankaful maximum security prison, Ghana - Elijah Tukwariba Yin (Masyarakat, Kebudayaan dan Politik, 2022)
In the field of penology, very few studies have paid attention to the role of religion in prison. The sparse scholarly studies are largely focused on the advanced countries, and rarely on prisons in Africa. In addition, the findings on the impact of religion on inmates have yielded mixed results. This study examined the role of religion as a facet of inmates’ social relationships. It is argued that the decision of inmates to participate in religious activities is not necessarily for redemption but for materialism. The study settled on a mixed method approach to data collection. The data revealed that inmates who participated in religious activities did so purposely for the material benefits associated with the practice of religion. Religion provided inmates the context for contemplating their lives and mortality. The study concludes that religious beliefs and practices; regardless of how it comes to be experienced within the confines of the prison, are powerful forces that influence the conduct of prisoners, prison officials and civil society organisations.